Clinical effects of Bifidobacterium as a probiotic on oral health: A systematic review - M Y Jayachandra; R Gayathiri; C N Aruna; Padma K Bhat; P M Arumugam (Wolters Kluwer Medknow Publications, 2023)
Background: The burden of oral diseases is increasing, which constitute a major public health problem. The use of probiotics as an adjuvant, along with routine dental care practice by an individual, can produce additional benefits in the maintenance of one's oral health. The study aimed to investigate the effect of Bifidobacterium as a probiotic on oral health. Material and Methods: Six databases and registers were searched from the start of the database to December 2021 without any restrictions. Randomized controlled trials (RCTs) evaluating the clinical effects of Bifidobacterium as a probiotic on oral health were included in the study. The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines were followed to conduct this systematic review. The included studies were analyzed for the risk of bias using the Cochrane risk-of-bias tool for randomized trial (RoB 2) tool as well as quality of available evidence using GRADE criteria. Results: From the 22 qualified studies, four studies showed non-significant results. There was a high risk of bias in 13 studies and some concerns of bias in nine studies. No adverse effects were reported, and the quality of available evidence was moderate. Conclusion: The effect of Bifidobacterium on oral health is questionable. Further high-quality RCTs are required on the clinical effects of bifidobacteria and also the optimum level of probiotic needed, and ideal mode of administration to provide oral health benefits. Furthermore, synergistic effects of the combined use of various strains of probiotics need to be studied.